2018
DOI: 10.1177/1077801218793226
|View full text |Cite
|
Sign up to set email alerts
|

Is Women’s Fear of Crime Fear of Sexual Assault? A Test of the Shadow of Sexual Assault Hypothesis in a Sample of Swedish University Students

Abstract: Prior research shows that women's higher fear of crime compared with men can largely be explained by women's fear of rape. Whether women's higher fear can also be explained by fear of nonviolent sexual harassment has not been explored. This study tested the shadow of sexual assault hypothesis in a sample of almost 3,000 Swedish university students. Our results confirm previous tests of the shadow thesis on the effect of fear of rape. In addition, we show that fear of sexual harassment also explained difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
5
29
0
4
Order By: Relevance
“…The effects of other physical space victimization (childhood victimization and stalking) were significantly higher for women than for men. This finding is consistent with Mellgren and Ivert’s (2019) empirical examination of the shadow of sexual assault hypothesis, which suggests that women, regardless of prior victimization, report fearing victimization more than men do. Further research on the specific characteristics of men, in particular, is required to gain additional insight into which groups are at risk of sexual assault and harassment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The effects of other physical space victimization (childhood victimization and stalking) were significantly higher for women than for men. This finding is consistent with Mellgren and Ivert’s (2019) empirical examination of the shadow of sexual assault hypothesis, which suggests that women, regardless of prior victimization, report fearing victimization more than men do. Further research on the specific characteristics of men, in particular, is required to gain additional insight into which groups are at risk of sexual assault and harassment.…”
Section: Discussionsupporting
confidence: 88%
“…Further exploration through bivariate analyses revealed that despite comparable estimates of OIV for males and females, there was a sex difference for behaviors indicative of social control, with females scoring higher than males; this difference remained at the multivariate level indicating that being female is a predictor of social control net of the effects of other socio-demographic characteristics or past experiences of violent victimization. This expected finding lends some support to theoretical discussions (Brownmiller, 1975;Sheffield, 2007) and research pointing to the gendered nature of social control, as well as the shadow of sexual assault hypothesis that women fear victimization more than men do (Mellgren & Ivert, 2019). Previous studies have shown that women who fear sexualized attacks and street-level harassment (Perilloux et al, 2012;Pryor & Hughes, 2013) and those who have experienced a sexualized attack (Archer, 2019) are more likely to engage in precautionary avoidance behaviors similar to those used in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Berdasarkan wawancara tersebut, peneliti merasa tertarik untuk membahas fenomena ini lebih lanjut dengan berfokus kepada mahasiswi sebagai subyek penelitian. Tulisan ini dipicu oleh penelitian serupa mengenai hubungan antara lingkungan kampus, rasa takut dan jender (Day, 1994;Fisher & May, 2009;Mellgren & Ivert, 2018). Namun, berbeda dengan penelitian-penelitian sebelumnya yang membahas lingkungan kampus secara umum, penulis akan memfokuskan lingkup penelitian pada area ambang (threshold) kampus.…”
Section: Pendahuluanunclassified
“…Usia dan jender merupakan faktor penting pada tingkatan rasa takut terhadap tindak kejahatan (Fisher & May, 2009;Mellgren & Ivert, 2018).…”
Section: Kajian Literatur 211 Perempuan Dan Rasa Takut Akan Viktimunclassified
See 1 more Smart Citation